DNAR-08. THE ROLE OF SMARCAL1 AS A SYNTHETIC LETHAL VULNERABILITY IN ATRX-DEFICIENT GLIOMAS. (14th November 2022) - Waitkus, Matthew; Liu, Heng; Brown, Alexandrea; Strickland, Laura; Khambati, Taher; Fraley, Casey; Diplas, Bill; Keir, Stephen; Ashley, David
Abstract: Mechanisms to maintain telomere length over successive cell divisions are a requirement for cancer cell immortalization. Although many cancers maintain telomere length through the activation of telomerase, ~10-15% of human cancers use telomerase-independent mechanisms of telomere maintenance, termed Alternative Lengthening of Telomeres (ALT). In gliomas, the ALT phenotype is associated with loss-of-function mutations in the ATRX gene in IDH -mutant astrocytomas, adult and pediatric glioblastomas (GBM), high-grade astrocytomas with piloid features, and pleomorphic xanthoastrocytomas. In adult GBM, we previously identified a relatively rare subset of ALT-positive ATRX wildtype tumors that harbored loss-of-function mutations in the SMARCAL1 gene, and we found that loss of SMARCAL1 activity plays a causative role in the onset of ALT in these tumors. SMARCAL1 is an annealing helicase that localizes to sites of DNA damage and replication stress and catalyzes the reversal of stalled replication forks. To better understand the relationship between ATRX mutations, SMARCAL1 activity, and the ALT phenotype, we investigated the localization and function of SMARCAL1 in ALT-positive glioma cells and xenografts with native ATRX deficiency. We found that SMARCAL1 localizes to ALT-associated PML bodies in astrocytoma cell lines with concurrent ATRX and IDH1 mutations (derived from grade 3 and 4 tumors). Our data show that inducible suppression of SMARCAL1 via doxycycline-induced RNAi leads to increased DNA double-strand breaks, increased abundance of extrachromosomal telomeric repeats (c-circles), and increased sensitivity to irinotecan, a topoisomerase I inhibitor. In an orthotopic mouse model, SMARCAL1 depletion exhibited a chemosensitizing effect in combination with irinotecan against a patient-derived xenograft (astrocytoma, IDH -mutant Grade 4). Based on these data, we hypothesize that SMARCAL1 activity is critical for resolving ALT-associated replication stress in ATRX-deficient malignant gliomas. We therefore propose that SMARCAL1 functions as a synthetic lethal vulnerability in ATRX-deficient ALT-positive gliomas and that SMARCAL1 inhibition is a viable therapeutic strategy in these tumors.